2022
DOI: 10.3389/fonc.2022.871513
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Tumor Microenvironment: A Close Up of Tumor-Associated Macrophages and Neutrophils

Abstract: The importance of the tumor microenvironment (TME) in dynamically regulating cancer progression and influencing the therapeutic outcome is widely accepted and appreciated. Several therapeutic strategies to modify or modulate the TME, like angiogenesis or immune checkpoint inhibitors, showed clinical efficacy and received approval from regulatory authorities. Within recent decades, new promising strategies targeting myeloid cells have been implemented in preclinical cancer models. The predominance of specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 280 publications
1
13
0
Order By: Relevance
“…A further important potential lead for future treatment of PCa patients derived from our study is the observation that enhanced GP130 signaling was associated with high-grade immune cell infiltration at the tumor site. This infiltration included CD3 + ;CD8 + T-cells, neutrophils, and macrophages that are considered major drivers of anti-tumor immunity 49,69 , and was accompanied by an upregulation of adaptive and innate immune system-related gene sets. In general, PCa cells and those comprising its microenvironment are known to express and secrete molecules mediating immunosuppression, rendering PCa immune-cold 22 and thus not a good target for otherwise highly efficient immune-based therapies 70 .…”
Section: Discussionmentioning
confidence: 99%
“…A further important potential lead for future treatment of PCa patients derived from our study is the observation that enhanced GP130 signaling was associated with high-grade immune cell infiltration at the tumor site. This infiltration included CD3 + ;CD8 + T-cells, neutrophils, and macrophages that are considered major drivers of anti-tumor immunity 49,69 , and was accompanied by an upregulation of adaptive and innate immune system-related gene sets. In general, PCa cells and those comprising its microenvironment are known to express and secrete molecules mediating immunosuppression, rendering PCa immune-cold 22 and thus not a good target for otherwise highly efficient immune-based therapies 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, numerous studies have indicated that tumor-associated immune/inflammatory cells promote and accelerate metastasis by establishing an immunosuppressive microenvironment within primary lesions and suppressing tumor immune surveillance [ 34 ]. Notably, the terminology of TANs does not relate to a specific differentiation step and activation status [ 35 ] but neutrophils as the first mediators of inflammatory reactions can influence tumor progression, depending on the tumor microenvironment [ 36 ]. A study indicates that TANs recruit macrophages and Treg cells, contributing to an immunosuppressive microenvironment to promote HCC progression and chemoresistance [ 37 ].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…In parallel, there are also coexisted heterogeneous macrophage populations which influence both tumor growth and immune response in the tumor compartment [ 38 ]. M1-like macrophages are the subpopulation for anti-tumor immunity, whereas M2-like TAMs promote carcinogenetic progression and suppress immune response [ 36 ]. As the aberrant lipid metabolism can reprogram not only the cancer cells but also the surrounding non-cancer cells, TME is becoming very important research field to study lipid molecules contributing to cellular lipid metabolism reprogramming.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…This intercellular communication actively contributes to remodeling of the tumor microenvironment (TME) to facilitate tumor growth, invasion, and metastasis [ 7 ]. The importance of the TME in dynamic regulation of cancer progression is widely accepted [ 8 ]. Tumor-associated macrophages (TAMs) in the TME play important roles in the genesis, development, and prognosis of cervical cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%